Understanding the gap: a balanced multi-perspective approach to defining essential digital health competencies for medical graduates - Brett Sumner; Rachelle Martin; Tehmina Gladman; Tim J Wilkinson; Rebecca Grainger (BMC Medical Education)
Abstract Background Rapid technological advancements have left medical graduates potentially underprepared for the digital healthcare environment. Despite the importance of digital health education, consensus on essential primary medical degree content is lacking. Focusing on core competence domains can address critical skills while minimising additions to an already demanding curriculum. This study identifies the minimum essential digital health competency domains from the perspectives of learners, teachers, and content experts aiming to provide a framework for integrating digital health education into medical curricula. Methods We conducted focus groups with students (n = 17), and semi-structured interviews with medical educators (n = 12) and digital sector experts (n = 11) using video conferencing. Participants were recruited using purposive sampling. The data were analysed using framework analysis and inductive thematic analysis to identify common themes. Results Four core themes and eleven sub-themes were identified and aggregated into four essential competency domains: “Understand the Local Digital Health Ecosystem and Landscape”, “Safe, Secure and Ethical Information Literacy and Management”, “Proficiency in Digital Health Tools and Associated Technologies” and “Scholarly Research and Evidence-based Practice”. Medical educator and digital sector expert participants provided the greatest source of data for curriculum content consideration. Students demonstrated varying levels of aptitude, confidence, and interest in technology. Conclusion Our balanced engagement with learners, educators, and digital health experts enabled the identification of a context-relevant framework for the minimum essential digital health competence domains for graduating medical students. The identification of focused, clinically relevant core competencies makes them amenable to integration into an existing curriculum tailored to local contexts. This approach addresses limitations of restricted curricular space and accommodates varying student interests, confidence and aptitude in technology. The delivery approach should consider a student-centred adaptive modality that takes advantage of advances in artificial intelligence (AI) as an effective pedagogical tool.